(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
One-fourth of the population globally is infected utilizing a bacterial infection-tuberculosis (TB). TB remains the most contagious killer disease globally having 10 million people falling ill with TB. The transmission route of TB is through the air and when symptoms occur, Therefore, as a dentist we need to be aware of oral tuberculosis such that proper protocol can be followed in our daily practice. This article highlights the important oral manifestation of tuberculosis and its confirmed diagnostic criteria so that a dentist can follow all the guidelines for proper management of a tuberculosis-infected dental patient.